ANALISA PENGARUH PEMAHAMAN AKAN PSAK 45, DAN LATAR BELAKANG INTERNAL AKUNTAN TERHADAP KARIR AKUNTAN ENTITAS NIR-LABA PADA ORGANISASI ADVENT DI INDONESIA KAWASAN BARAT - Sihombing, Tanggor; Sihombing, Jenny (Jurnal Ekonomis, 2013)
This study aims to determine the understanding of the accountants to PSAK 45, and to investigate how accountants will influence the understanding of PSAK 45 and the background to a accountant career in non-profit organization by using a variance -based SEM. The findings indicate that the understanding of accountants to PSAK 45 is on average weight of 80.2 %, with a maximum weight of 90.3 % and in minimum weight of 70.3 %. Other findings also indicate that: for the accountants, to determine whether they will get a promotion or not (as a proxy of career), the understanding factors to PSAK 45 (as measured from 19 points questioner) is not significant. Yet the background of accountants is not significant (as measured from the high level of education and length of work ). Given the limited coverage of the object under this study, it is necessary to expand the research object on a larger scope and by adding latent variables so that the findings can be more generalized. Keywords: Non-Profit Organization, Accounting Standard, Certified Accountant, partial least square.